Analisis Kualitas Pelayanan Terhadap Kepuasan Pasien Rawat Jalan Di Puskesmas Tinambung Kabupaten Polewali Mandar - Aryanti, Novi; Irwan, Muhammad (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Purpose of this study was to determine and analyze of service quality dimensions of service quality are tangibles, reliability, responsiveness, assurance and empathy toward patient satisfaction partially or simultaneosly and to find out and analyze the most dominant dimensions of service quality. Method used accidental sampling. Data collection used questionnaires. The sample used in this study is 98 respondents.Data analysis method used quantitative analysis using validity and reliability test, F test, the coefficient of determination, t test and linear regression analysis. Results of this study showed that the quality of service that consists of tangibles (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) simultaneously significant effect on patient satisfaction. Partially, Responsiveness variable (X3) and Empathy (X5) showed significant effect on satisfaction (Y). While, variable Tangibles (X1), Reliability (X2) and Assurance (X4) partially did not show significant effect on satisfaction (Y). Keywords: tangibles, reliability, responsiveness, assurance, empathy